Some Nutritional Composition and Functional Properties of Prosopis Africana - Aremu, MO; Olonisakin, A; Atolaye, BO; Ogbu, CF (Bangladesh Journal of Scientific and Industrial Research, 2008)
The nutritional composition and functional properties of Prosopis Africana were studied using standard analytical techniques. The results gave proximate composition as follows: moisture, total ash, ether extract, crude protein, crude fibre and carbohydrate were 1.9, 4.4, 12.8, 23.6, 3.3 and 54.0g % respectively. The predominant mineral was K (617.5mg/100g sample) followed in the highest rank by Mg (420.1mg/10g sample). Other minerals such as Na, Ca, P, Mn, Cu, Zn, Fe and Cr were 110.7, 362.5, 196.4, 36.2, 46.2, 22.4, 15.5 and 0.2mg/100g sample respectively while Cd and Pb were not detected. Amino acid analysis revealed that the sample contained nutritionally useful quantities of most of the essential amino acids. The first limiting amino acid was Thr and predicted isoelectric point was 5.4. Functional properties results were: foaming capacity, 3.9 %, foaming stability 96.2 %; water absorption capacity, 340.0; oil absorption capacity, 120.0 %; emulsion capacity 30.0 mLg-1; emulsion stability 38.4 mLg-1; least gelation capacity, 16.0 % and bulk density 0.5268 mLg-1. The protein solubility of the P. Africana was found to have minimum solubility at pH 4.5. Key words: Nutritional composition, functional properties, Prosopis Africana Bangladesh J. Sci. Ind. Res. 42(3), 269-280, 2007